GUIDELINES FOR THE STUDY OF INNOVATION ACTIVITIES OF THE ENTERPRISES IN THE FOREST INDUSTRY - Popova, Radostina (Innovation in Woodworking Industry and Engineering design, 2015)
This report presents the specifics of the study of innovation of the enterprises of forest industry. It includes recommendations for distinguishing innovation activities in product and process innovations, organizational and marketing innovations, and eco-innovations. The report presents typical examples of innovation activities in the furniture sector and activities that are not considered for innovative